The Use of An Example of People's Oral Creation and Modeling Technologies in The Development of Creative Thinking of Students During Learning the Uzbek Language in Primary School - Tosheva Dildora Abdumalikovna; Joraeva Nargiza Oktamovna (Zien Journals, 2021)
This article addresses issues such as the formation of creative thinking of students in primary school, individual approach to students, the development of creative thinking of students using examples of folklore and modeling. The teacher-student relationship in mother tongue education and the factors that set it on the right path are analyzed.
Keywords: Modeling; Pedagogical Technology; Creativity; Creative Thinking